EFFICIENCY OF ULTRASOUND STUDY IN THE DIAGNOSIS OF CHOLANGIOCELLULAR CARCINOMA - T. Yu. Danzanova; G. T. Sinyukova; P. I. Lepedatu; N. E. Kudashkin (Вестник рентгенологии и радиологии)
Objective: to evaluate the efficiency of ultrasound diagnosis in detecting and staging cholangiocellular carcinoma.Material and methods. An ultrasound study (USS) was conducted in 120 patients aged 19 to 84 years with cholangiocellular carcinoma. The patients were divided into 3 groups by the location of a tumor process: 1) 47 (39.2%) patients with intrahepatic tumor; 2) 49 (40.8%) with portal duct or Klatskin’s tumor; 3) 24 (20%) with distal one. Ninety (75%) patients were operated on; the others underwent minimally invasive X-ray surgical interventions as percutaneous transhepatic cholangiostomies. The data of ultrasound diagnosis were compared with the results of other studies, intraoperative assessment and morphological examination of a removed gross specimen.Results. A tumor was detectable by USS only in 90 (75%) patients; its sensitivity was 100% for intrahepatic cholangiocellular carcinoma; 69.4 and 37.5% for portal duct and distal ones, respectively. It is most difficult to diagnose distal carcinomas of the common bile duct. USS reveals no semiotic signs of intrahepatic cholangiocellular carcinoma, which could distinguish the latter from other liver cancers. The specific features of the infiltrative growth of a bile duct tumor, such as hyperechoic infiltration along the external outlines of the ducts or hypoechoic infiltration during thickening of the duct walls, were ascertained. The sensitivity of intraoperative USS in identifying intrahepatic and portal duct cholangiocarcinoma was 100%. That of USS in detecting lymph node metastases was 61%; we developed the semiotics of altered metastatic lymph nodes.Conclusion. The findings have indicated the high informative value of ultrasound diagnosis in determining the dilatation of the bile ducts and the spread of a tumor to the liver and lymph nodes. It is recommended that the indications for intraoperative USS should be expanded in intrahepatic cholangiocellular carcinoma to define the extent of duct carcinoma.